Genes Expressed Differentially in Hessian Fly Larvae Feeding in Resistant and Susceptible Plants - Chen, Ming-Shun; Liu, Sanzhen; Wang, Haiyan; Cheng, Xiaoyan; El Bouhssini, M.; Whitworth, R. Jeff (My University, 2016)
The Hessian fly, Mayetiola destructor, is a destructive pest of wheat worldwide and mainly controlled by deploying resistant cultivars. In this study, we investigated the genes that were expressed differentially between larvae in resistant plants and those in susceptible plants through RNA sequencing on the Illumina platform. Informative genes were 11,832, 14,861, 15,708, and 15,071 for the comparisons between larvae in resistant versus susceptible plants for 0.5, 1, 3, and 5 days, respectively, after larvae had reached the feeding site. The transcript abundance corresponding to 5401, 6902, 8457, and 5202 of the informative genes exhibited significant differences (p <= 0.05) in the respective paired comparisons. Overall, genes involved in nutrient metabolism, RNA and protein synthesis exhibited lower transcript abundance in larvae from resistant plants, indicating that resistant plants inhibited nutrient metabolism and protein production in larvae. Interestingly, the numbers of cytochrome P450 genes with higher transcript abundance in larvae from resistant plants were comparable to, or higher than those with lower transcript abundance, indicating that toxic chemicals from resistant plants may have played important roles in Hessian fly larval death. Our study also identified several families of genes encoding secreted salivary gland proteins (SSGPs) that were expressed at early stage of 1st instar larvae and with more genes with higher transcript abundance in larvae from resistant plants. Those SSGPs are candidate effectors with important roles in plant manipulation.
Citation: Chen, M. S., Liu, S. Z., Wang, H. Y., Cheng, X. Y., El Bouhssini, M., & Whitworth, R. J. (2016). Genes Expressed Differentially in Hessian Fly Larvae Feeding in Resistant and Susceptible Plants. International Journal of Molecular Sciences, 17(8), 14. https://doi.org/10.3390/ijms17081324
Keywords: Plant Resistance; Effectors; Compatible Interaction; Incompatible; Interaction; Salivary Glands